Enfermedad poliquística hepatorrenal complicada con suboclusión intestinal: Reporte de un caso.: Hepatorenal polychistic disease complicated with intestinal suboclusion: A case report. - Salinas Calderón, Jonathan Alexander (2022)
Autosomal Dominant Polycystic Kidney Disease, known by its acronym ADPKD (Autosomal Dominant Polycystic kidney disease), is a condition of genetic origin characterized by two types of mutations in the PKD1 and PKD2 genes that code for polycystins (PC) 1 and 2, respectively. It is associated with extrarenal manifestations, both cystic and non-cystic; the liver is the most affected organ within the cystic manifestations; as well as cerebral vascular alterations, in non-cystic ones. We report a 44-year-old woman with polycystic hepato-renal disease (PLKD) complicated by intestinal subocclusion.